2017
DOI: 10.1021/acsmacrolett.7b00756
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassical Spherical Packing Phases Self-Assembled from AB-Type Block Copolymers

Abstract: Among the various ordered morphologies self-assembled from block copolymers, the spherical packing phases are particularly interesting because they resemble the familiar atomic crystals. The commonly observed spherical morphology of block copolymers is the body-centered-cubic phase. Recently, a number of novel spherical packing phases, i.e., the complex Frank–Kasper phases originally obtained in metallic alloys, have been observed in block copolymer melts. Theoretical studies have revealed that conformational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 53 publications
4
115
0
1
Order By: Relevance
“…Grason also found that AB n miktoarm stars with high n can highly distort the interface of HPC toward the hexagonal assembly of the Voronoi cell in region where the hexagonal cylinder phase normally stands . Furthermore, more novel structures such as new Frank‐Kasper phases, that is, Laves phases of C14 and C15, and and so forth, were recently predicted using SCFT studies …”
Section: Introductionmentioning
confidence: 95%
“…Grason also found that AB n miktoarm stars with high n can highly distort the interface of HPC toward the hexagonal assembly of the Voronoi cell in region where the hexagonal cylinder phase normally stands . Furthermore, more novel structures such as new Frank‐Kasper phases, that is, Laves phases of C14 and C15, and and so forth, were recently predicted using SCFT studies …”
Section: Introductionmentioning
confidence: 95%
“…Theoretical studies predict that by making branched architectures, AB n -star-typeb lock polymers could form nontraditional morphologies such as Frank-Kasper phases. [30] Conformationala symmetry was believed to play ac entral role in such systems. By increasing the number of tails attached on the DPOSS head, researchers found that not only was phase boundary shift observed, but also there appeared aw indow of unusual A15, s,a nd DQC phases located between traditional HEX and BCC phases.…”
Section: Topo-isomersmentioning
confidence: 99%
“…Successful extension of this paradigm to other FK phaseforming soft materials is highly likely, and here it could provide an attractive alternative to methods being employed with block copolymers and blends of block copolymers that rely on empirically-driven thermal processes that involve long isothermal annealing times and mass transfer of polymeric components within the melt or disordered state to secure various soft matter FK and dodecagonal quasi-crystal (DDQC) phases. [2,4,11] As a final consideration, for the full utility of small molecule modulation as a strategy for obtaining soft matter FK phases to be realized, the specific role(s) played by 2 in the present system must be unequivocally determined. At this stage, it is reasonable to assume that 2 resides within the aPMP domain of 1, and potentially, with the methylated phenol moiety preferentially located near the sugar-polyolefin interface.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thermotropic one-component soft-matter Frank-Kasper (FK) phases are fascinating topologically close-packed (TCP) periodic structures that arise in the condensed state through the reconfiguration and self-sorting of deformable sphere-shaped particles into two or more crystallographically distinct sets with different coordination number, size, or shape. [1][2][3][4][5][6][7][8][9][10][11] On the other hand, the small set of currently known thermotropic FK phases that have now been experimentally established over the past 20 years for a range of different soft materials are largely of structural interest, and with only a few rare examples that can be viewed as coupling form with function. [12] Very recently, we reported that the sugar-polyolefin conjugate, cellobiose-triazole-linked atactic poly(4-methyl-1-pentene) (CB-aPMP) (1), undergoes an irreversible thermotropic order-order transition from an initial hexagonal cylindrical (C) morphology to produce a cubic FK A15 (Pm3 n) phase with the unit cell shown in Figure 1.…”
mentioning
confidence: 99%